2013
DOI: 10.1007/s13204-013-0276-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nano structured Ba2SnO4 as a novel photocatalyst material for the chromate reduction

Abstract: The photo-electrochemical properties of the layered perovskite Ba 2 SnO 4 , prepared by nitrate route are reported for the first time. The oxide exhibits a direct optical transition at 2.98 eV, attributed to the charge transfer O 2-: 2p ? Sn 4? : 5s and possesses a chemical stability over the whole pH range. The Mott Schottky plot in acidic medium is characteristic of n type conductivity with a flat band potential E fb of -0.84 V SCE and an electron density N D of 1.14 9 10 17 cm -3 . The electrochemical imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Extrapolating the linear portion of the curve to the x-axis provides the direct and indirect band gap values. The values of direct band gap for undoped sample obtained in this work is in agreement with the values reported in the literature [42,43]. The value of direct bandgap was found to be 3.75 eV, 3.23 eV, 3.28 eV and 3.30 eV and indirect bandgap to be 3.26 eV, 2.92 eV, 3.04 eV and 3.05 eV for samples B2LS0, B2LS1, B2LS2 and B2LS4 respectively.…”
Section: Uv-absorption Spectroscopysupporting
confidence: 91%
“…Extrapolating the linear portion of the curve to the x-axis provides the direct and indirect band gap values. The values of direct band gap for undoped sample obtained in this work is in agreement with the values reported in the literature [42,43]. The value of direct bandgap was found to be 3.75 eV, 3.23 eV, 3.28 eV and 3.30 eV and indirect bandgap to be 3.26 eV, 2.92 eV, 3.04 eV and 3.05 eV for samples B2LS0, B2LS1, B2LS2 and B2LS4 respectively.…”
Section: Uv-absorption Spectroscopysupporting
confidence: 91%
“…Furthermore, tin-based perovskite materials have widely been used in hydrogen production, which attracted significant scientific attention. In this regard, Chen et al explored rod- and dumbbell-shaped SrSnO 3 perovskite materials and utilized them in water splitting with an efficient photocatalytic activity . Similarly, Omeiri et al studied BaSnO 3 for the photocatalytic function of hydrogen evolution under visible light . Additionally, Zhang et al reported MSnO 3−δ materials for hydrogen production .…”
Section: Introductionmentioning
confidence: 99%
“…So, the strategy is to synthesize the oxide by chemical route in order to shorten the path the photocarriers have to diffuse to reach the interface. In this respect, a considerable improvement has been made in the synthesis of photoactive materials with small crystallite sizes and large specific surface areas [11][12][13]. With the advent of nanotechnology, the sol-gel method has gained recognition in the solid-state chemistry and a review of advantages has been given recently by Koseva [14].…”
Section: Introductionmentioning
confidence: 99%